Utilization Pattern of ICT Tools by Paddy Growers in Uttar Pradesh - Kumar, Sudheer; Singh, Mayank; Singh, Prakash; Rohit, (Indian Journal of Extension Education, 2023)
Information and Communication Technology (ICT) in agriculture refers to the process of making available ICTs to assist, enhance, and optimise the dissemination of knowledge among the farmers. This study was conducted during 2018-19 in Sultanpur district of Uttar Pradesh. Due to the district’s significant area under rice cultivation, Sultanpur in Uttar Pradesh was chosen as the location of the research. For the sampling a total of 120 farmers, from five villages were selected randomly by using proportionate random sampling technique. ICT utilization among the farmers was the maximum and 45.83 per cent respondents were using ICT tools to a medium extent, and the mobile was the most utilized ICT tool, ranking first with a mean score value of 6.99. In contrast to age, caste, family type, social involvement, and material ownership, this showed non-significant and negative correlations with the extent to which ICT tools were used. The variable ‘education’ had a very significant and positive correlation with the use of ICT tools that mainly effect the utilization of ICT tools 19. The utilization extent of ICT tools was satisfactory but still there was need of awareness and educational programmes to be introduced in study area.
Keywords: ICT tools; Paddy grower; Utilization; Uttar Pradesh